(untitled) (American Journal of Arts and Human Science, 2023)
Premarital sex can be both fulfilling and detrimental to college students. Studies were conducted on the factors that induced premarital sex among college students. However, no study has been conducted yet, regarding maritime students-based factors affecting premarital sex decisions in the Philippines. The objective of this study is to provide the general public, especially the student-readers, an idea of the extent of the factors affecting decisions not to engage in premarital sex among maritime first-year students in Cebu, Philippines. Three hundred sixty maritime first-year students were selected from the University of Cebu maritime department of S.Y. 2020-2021. A descriptive-quantitative method of research without experimentation was utilized. Systematic random sampling was used to establish the sample size. A modified survey questionnaire adopted from the study was used as the main instrument. Percentages and frequency counts were used to calculate and interpret the data. Results revealed that most respondents were not involved in premarital sexual activities. The major factors affecting their decisions not to engage in premarital sex are family values, followed by religious doctrines. The results of the study will also enrich literature in as much as it will give numbers and facts as bases to the Philippine Commission for Higher Education, college institutions, and ethics teachers in the Philippines to promote the use of books and the creation of teaching materials that tackle more lessons on sexuality, family and religious values to reinforce the Filipino maritime students for the present and future moral challenges.